Digital Marketing Sebagai Strategi Pemasaran UMKM Di Desa Kemiri Kidul - Dwi Jatmoko; Basuki Basuki; Joko Purwanto; Nur Hidayati; Ari Fajar Isbakhi; Aci Primartadi (BADAN PENERBIT STIEPARI PRESS, 2023)
The rapid development of digital world technology and the internet of course also has an impact on the world of marketing. Especially digital marketing because it allows potential customers to obtain all kinds of information about products and make transactions via the internet.Community Service Partners in this activity are Micro, Small and Medium Enterprises (MSMEs) which are engaged in the business of producing and buying and selling various kinds of batik cloth and food. Kemiri Kidul Village UMKM, which is almost 10 years old. In terms of marketing activities, it is still very minimal and conventional. For this reason, MSMEs need to be given socialization about the importance of using digital marketing so that their marketing system becomes better. The aim of this activity is to provide outreach and assistance to MSMEs in Kemiri Kidul Village regarding the implementation of Digital Marketing as a strategy in marketing products.